Electric-field control of Josephson oscillations in dipolar Bose-Einstein condensates - Romero-Huenchunir, G; Galvez-Poblete, D (American Physical Society, 2025)
We study the dynamic behavior of a Bose-Einstein condensate (BEC) with dipolar interactions when the influence of external electric fields affects the coherent tunneling properties. Here, we propose a tunable platform based on BECs where Josephson oscillations can be engineered and modulated through external electric fields. We develop a theoretical and numerical framework that reveals how electric fields affect intercondensate tunneling, phase dynamics, and collective excitations. By employing a coupled set of Gross-Pitaevskii equations with adiabatic elimination of excited states, we demonstrate field-induced tuning of Josephson frequencies and a transition from contact to dipole-dominated regimes. These findings corroborate theoretical predictions about the sensitivity of dipolar BECs to external fields and deepen our understanding of quantum coherence and tunneling in long-range interacting quantum systems.